Identifikasi kesulitan siswa dalam memecahkan masalah geometri berdasarkan tingkatan berfikir Van Hiele - Mahfudy, Sofyan; Afriana, Hanna (Jurnal of Math Tadris, 2024)
Several previous studies have shown students' low achievement in learning Geometry. However, the diversity of students' abilities affects their perspectives and ways of thinking in the learning process. Investigation of students' difficulties in solving Geometry problems based on their level of thinking is necessary to gain actual knowledge. Identifying student difficulties will help the teacher design effective lessons to address these issues. This research aims to identify and describe students' difficulties in solving geometry problems based on Van Hiele's level of thinking. This study used a qualitative approach with data analysis that entailed data reduction, data presentation, and conclusion. The subjects of this study were 3 students in the second academic year in junior high school who were purposively selected from 15 students who participated in the Van Hiele thinking levelling test. The results show that the stage of Van Hiele's thinking that students have achieved was Level 2 (informal conclusion). Students with Level 0 of thinking tend to have difficulty on understanding the concept of area of geometric shapes and unable to develop problem solving steps. Meanwhile, students at Level 1 had difficulty in obtaining alternative solutions to the problem of the concept of the area of geometry.